Editorial Information - Editors, PJLS (Polskie Studia Krajobrazowe, 2019)
Guest Editor: Monika Weychert Translation: Szymon Nowak Proof reading: Kamil Lemanek Graphic Design: Ewa Mikuła, Katarzyna Turkowska Typesetting: Monika Rawska / Legut